(untitled) (Communications in Computational Physics, 2018)
Red blood cells can recover their resting shape after having been deformed by shear flow. Their rims are always formed by the same part of the membranes, and the cells are said to have shape memory. Modeled as two-dimensional elastic capsules, their recovery motion and shape memory is studied, mainly focused on the effect of the spontaneous shape. The fluid-structure interaction is modeled using immersed boundary method. Based on the simulations, the resting shapes of capsules are obtained and the area ratio of spontaneous shape is found to play an important role. After remove of shear flow, all capsules can recover their resting shapes, while only capsules with noncircular spontaneous shapes present shape memory. As the spontaneous shape approaches a circle but still noncircular, the capsule spends more time on recovery process. We consider how these capsules deform depending on the membrane bending energy, and find that the relaxation speed is positive correlated to the range of values of dimensionless bending energy. These results may help to identify different spontaneous shapes for capsules especially RBCs through future experiments.